Clinical Characteristics Associated with Physical Violence in the Elderly: A Retrospective Multicenter Analysis - Dong Hoon Lee; Sang Soo Han; Duk Ho Kim; Eui Chung Kim; Eun Hae Lee; Ju Ok Park; Choung Ah Lee (Tehran University of Medical Sciences, 2022)
Background: Elder abuse is predicted to increase with the rapid population ageing in many countries. Violent injury is influenced by individual factors as well as interpersonal and social relationships, with different manifestations based on changes in the socioeconomic position of older adults. We comparatively investigated the clinical and injury characteristics of physical violence in the elderly with those in another age group. Methods: We included elderly patients (age ≥65 years) who visited six emergency departments (ED) with violence-induced injuries in 2017. The control group comprised patients aged 45-64 years, selected by 1:2 matching based on hospital and sex. Data were extracted from the National Emergency Department Information System and electronic medical records. Both groups were compared for injury mechanism, injury location, activity during injury, diagnosis, and clinical outcomes. Results: Among the 316,944 patients who presented to the 6 ED, 89,178 (28.1%) had traumatic injuries, and 1.6% and 4.5% of injuries were sustained due to violence in the ≥65 and 45-64 year age groups, respectively. There were no significant intergroup differences in the perpetrator (P=0.27), body parts affected (P=0.63), and diagnosis (P=0.23), whereas the older adult group had a significantly higher proportion of traumatic injury by fall (P=0.01), at road and traffic facilities (P=0.01), during work (P=0.01), and multiple injuries (P<0.01). Conclusion: The increase in non-regular workers in the elderly after retirement may have increased the risk of traumatic workplace injuries. As workplace injuries may be a new risk factor for physical violence in the elderly, institutional workplace injury prevention policy is needed.